2009
DOI: 10.1007/s00330-009-1642-9
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of end-systolic reconstructions in coronary dual-source CT angiography for high heart rate patients

Abstract: Our data suggest that CT with a temporal window below 100 ms may provide acceptable systolic reconstructions at any heart rate, in a large proportion of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Similarly, a shift of optimal image quality from diastolic to systolic reconstruction intervals in patients with high HRs is reported for 64-detector single-source as well as 64-detector dual-source retrospectively ECG-gated CTCA [12][13][14][15][16][17][18]. Using retrospectively ECG-gated DSCT, Adler et al [17] found the optimal systolic phase of image reconstruction to be between 35% and 50% of the RR interval in patients with HR>65 bpm and Araoz et al [16] reported that optimal image sharpness of the coronary arteries is achieved at 65-70% of the RR interval in patients with HR≤70 bpm and at 35-40% of the RR interval in patients with HR>70 bpm. For systolic image acquisition, we chose the 30% interval for initiation of imaging of the cranial-most slices of the heart, in order to achieve data acquisition of the mid to distal RCA-the segments most affected by motion artefacts [13]-within a range of 35-50% of the RR interval.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Similarly, a shift of optimal image quality from diastolic to systolic reconstruction intervals in patients with high HRs is reported for 64-detector single-source as well as 64-detector dual-source retrospectively ECG-gated CTCA [12][13][14][15][16][17][18]. Using retrospectively ECG-gated DSCT, Adler et al [17] found the optimal systolic phase of image reconstruction to be between 35% and 50% of the RR interval in patients with HR>65 bpm and Araoz et al [16] reported that optimal image sharpness of the coronary arteries is achieved at 65-70% of the RR interval in patients with HR≤70 bpm and at 35-40% of the RR interval in patients with HR>70 bpm. For systolic image acquisition, we chose the 30% interval for initiation of imaging of the cranial-most slices of the heart, in order to achieve data acquisition of the mid to distal RCA-the segments most affected by motion artefacts [13]-within a range of 35-50% of the RR interval.…”
Section: Discussionmentioning
confidence: 61%
“…The optimal timing of image acquisition to minimise coronary arterial motion artefacts-especially of the mid to distal right coronary artery (RCA)-may shift to systolic intervals in patients with high HRs as diastolic diastasis shortens and eventually disappears with increasing HRs [9,10]. It has been demonstrated with 16-and 64-detector single-source as well as dual-source CT that the best results regarding coronary artery image quality are achieved at middiastolic intervals in patients with low HRs and at systolic intervals in patients with high HRs [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Leschka et al found the best diagnostic image quality in the diastolic phase between 50% and 80% of the cardiac cycle for HRs <85.5 bpm on 64-slice CT [21]. However, at higher HRs reconstructions of several phases of the RR interval may commonly be necessary to obtain diagnostic image quality of all coronary segments [16,22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Second, instead of triggering the coronary CT angiography in the diastolic phase of the cardiac cycle, we evaluated the feasibility of triggering the acquisition in systole. In fact, the systolic phase has demonstrated to be the optimal reconstruction phase for conventional retrospectively ECG-gated coronary DSCT examinations performed in subjects with high heart rates [9,21,33]. In a study performed in 20 consecutive heart transplant recipients undergoing retrospectively ECGgated coronary DSCT angiography Bastarrika et al [9] observed that systolic reconstruction intervals provided better image quality of the coronary arteries than diastolic reconstruction intervals, thus emphasizing the need of systolic acquisitions in this specific patient population.…”
Section: Discussionmentioning
confidence: 99%
“…This acquisition mode has shown to hold equivalent diagnostic accuracy in detecting significant coronary artery disease as compared with the regular retrospectively ECG-gated technique [16][17][18]. As reported in the literature, however, prospectively ECG triggered CT angiography may only be feasible in patients with low and regular heart rates [19], whereas retrospectively ECG-gated coronary CT angiography with systolic reconstructions has been recommended for patients with elevated heart rates [20][21][22] and/or insufficient response to beta-blocker premedication, such as heart transplant recipients [23].…”
Section: Introductionmentioning
confidence: 99%